2019
DOI: 10.1177/2397847319855087
|View full text |Cite
|
Sign up to set email alerts
|

Ten-day and four-week toxicity and toxicokinetics studies of alpha-glycosyl isoquercitrin in juvenile Göttingen minipigs

Abstract: Background: Alpha-glycosyl isoquercitrin (AGIQ) is widely used as an anti-oxidative food additive in many products. Nevertheless, information on its safety and toxicity is still very limited. A 90-day toxicity study in rats and comprehensive genotoxic studies have proven AGIQ to be safe. Aim: The goal of this study was to assess the safety of use of AGIQ in infant formula. To test for potential adverse effects on growth or other safety issues specific for young animals, we performed a 10-day and a 4-week study… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 30 publications
0
7
0
Order By: Relevance
“…The primary purpose of this study was to determine the AGIQ metabolite responsible for the yellow bone discoloration previously noted in dietary exposure studies of AGIQ in rats (Nyska et al 2016;Tamano et al 2001), which has also been noted in minipig studies of AGIQ (Maronpot et al 2019). The absence of effects on survival, clinical condition, body weight, and food consumption and the presence of dose-dependent yellow femur discoloration at all dose levels in this study generally corroborated the results reported for those studies, with the exception of the decreased body weights observed in female rats at a dose level of 2.5% in one study (Tamano et al 2001).…”
Section: Discussionmentioning
confidence: 95%
“…The primary purpose of this study was to determine the AGIQ metabolite responsible for the yellow bone discoloration previously noted in dietary exposure studies of AGIQ in rats (Nyska et al 2016;Tamano et al 2001), which has also been noted in minipig studies of AGIQ (Maronpot et al 2019). The absence of effects on survival, clinical condition, body weight, and food consumption and the presence of dose-dependent yellow femur discoloration at all dose levels in this study generally corroborated the results reported for those studies, with the exception of the decreased body weights observed in female rats at a dose level of 2.5% in one study (Tamano et al 2001).…”
Section: Discussionmentioning
confidence: 95%
“…The primary metabolites of EMIQ thus far detected in plasma after oral administration to animals and humans are QU conjugates. Some methylated derivatives have also been detected, in particular the conjugates of isorhamnetin and tamarixetin ( Figure 3 , Table 1 ) [ 10 , 13 , 45 , 46 ]. The transformation of QU to glucuronides and sulfates mostly takes place in the enterocytes due to the action of UDP-glucuronosyltransferase and phenol sulfotransferase, respectively [ 42 , 44 ].…”
Section: Metabolism Absorption and Bioavailabilitymentioning
confidence: 99%
“…Compared to untreated control animals, there were no effects on weight gains and food consumption and no significant differences in hematological parameters and organ weights. The histological examination did not reveal any pathologies that could be related to the EMIQ-administration [ 46 ]. No severe adverse effects were found during a 4-week treatment with the same doses of EMIQ.…”
Section: Safetymentioning
confidence: 99%
See 1 more Smart Citation
“…8,9 Previous toxicity assessments have shown that AGIQ is safe, non-carcinogenic, and non-genotoxic, 5,7,[10][11][12][13] but some of the earlier studies used incompletely characterized AGIQ and/or did not adhere to current Good Laboratory Practice (GLP). 6,10,12,13 Due to the current effort to expand the use of AGIQ in the consumer food and beverage industry, recent GLP-compliant studies of high-purity AGIQ (including comprehensive genotoxic assessment, 7 10-day and 4-week studies in preweaning Göttingen minipigs, 14 and a 90-day study in rats) 5 were conducted to augment the older toxicity database. These studies have generally confirmed the safety profile of AGIQ.…”
Section: Introductionmentioning
confidence: 99%